2015
DOI: 10.1371/journal.pone.0132352
|View full text |Cite
|
Sign up to set email alerts
|

Expression Quantitative Trait Loci for CARD8 Contributes to Risk of Two Infection-Related Cancers—Hepatocellular Carcinoma and Cervical Cancer

Abstract: Caspase recruitment domain family, member 8 (CARD8) can coordinate innate and adaptive immune responses and sensitize cells to apoptosis, which may participate in tumorigenesis of virus-induced hepatocellular carcinoma (HCC) and cervical cancer. By bioinformatics analyses, we identified several single nucleotide polymorphisms (SNPs) within a new identified long non-coding RNA (lncRNA) as expression quantitative trait loci (eQTLs) for CARD8. In this study, we therefore hypothesized that CARD8 eQTLs SNPs within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…LncRNA AC008392.1, located in the upstream region of CARD8, may affect the normal expression of CARD8. 41 CARD8 may influence the tumor biology by inhibiting cell apoptosis 32 , 53 and involving the NF-kB pathway. 54 In dbSNP database, the MAF of rs7248320 in the Chinese population was 0.402 (MAF >0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LncRNA AC008392.1, located in the upstream region of CARD8, may affect the normal expression of CARD8. 41 CARD8 may influence the tumor biology by inhibiting cell apoptosis 32 , 53 and involving the NF-kB pathway. 54 In dbSNP database, the MAF of rs7248320 in the Chinese population was 0.402 (MAF >0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNA AC008392.1 is found in many cell lines including human B lymphocyte and human cervical cancer cells. 41 Some studies have demonstrated that rs7248320 in AC008392.1 may represent the expression quantitative trait loci (eQTL) for CARD8. Hence, it may change the expression of CARD8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Followingthe traditional method[18], genomic DNA was extracted from a leukocyte pellet by a series of treatments. Then, all SNPs were genotyped using the Sequenom Mass ARRAY iPLEX platform (SequenomInc).…”
Section: Methodsmentioning
confidence: 99%
“…The genomic DNA was extracted from the leukocyte pellet by a series of treatments using conventional methods [14] . Then, we use the Sequenom Mass ARRAY iPLEX platform (Sequenom Inc) to genotype the SNP rs4733586.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%